Dimensions of stock market liquidity: empirical evidence of a frontier market - Pham, Khang Quac (Wymiary płynności rynku papierów wartościowych: weryfikacja empiryczna na rynku granicznym, 2020)
The paper presents a discussion of stock market liquidity in a frontier market after the financial crisis. The paper defines the dimensions of stock market liquidity and indicates possible liquidity measures which could be applied to analyze liquidity on the stock exchange in Vietnam. The empirical result shows the aggregate liquidity, which captures various dimensions of liquidity through eight liquidity measures based on a daily basis during the period from 2011 to 2018. The analysis indicates the characteristics of liquidity in the Vietnamese stock market, and the differences in liquidity among three market capitalization groups: small, medium, and large. It is evident that there are differences in the three sizes of companies, where larger companies are found to have better liquidity
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 2, s. 72-80
Keywords: frontier market; depth dimension; tightness dimension; resilience dimension; rynek graniczny; wymiar głębokości; wymiar szczelności; wymiar elastyczności